Changes in dietary habits and prevalence of cardiovascular risk factors among school students in Macao, China. Issue 6 (November 2019) - Keung, Vera; Lo, Kenneth; Cheung, Calvin; Tam, Wilson; Lee, Albert
Abstract: Objective: Given the increasing burden of childhood obesity, it is important to examine the changes in dietary habits and prevalence of cardiovascular risk factors among Macao students. Methods: A cross-sectional study was conducted among primary and secondary school students in Macao, China in 2014–2015 with addition to data collected from 2008 to 2009 for comparison. The dietary behaviours, prevalence of obesity and dyslipidaemia were compared by study period. Subjects: In 2014–2015, dietary assessment was conducted among 3635 students, physical assessment was conducted among 1427 school students. In 2008–2009, dietary assessment was conducted among 4271 students, physical assessment was conducted among 1700 school students. Results: When compared with students in 2008, higher percentage of students from present study period consumed dairy products, crispy food and chocolate, while fewer students had fruits, vegetables and fried food at least once every day. Despite lower prevalence of elevated total cholesterol and low-density-lipoprotein cholesterol, the rate of general obesity, low high-density-lipoprotein cholesterol and hyperglycaemia has increased significantly in 2014–2015. Students aged 12–14 consumed less fruits and vegetables and suffered from higher rate of general and abdominal obesity, as well as low high-density-lipoprotein cholesterol and elevated serum triglycerides in 2014–15. Conclusions: The students' diet had both favourable and unfavourable changes. The rate of obesity and dyslipidaemia rises, while the situation for students aged 12–14 is more concerning.